Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane

Solvent free, environment benign synthesis of 1,4-dihydropyridines and polyhydroquinolines by using heterogeneous Zn/MCM-41 catalyst - Dhengale, Shankar D.; Naik, Vaibhav M.; Kolekar, Govind B.; Rode, Chandrashekhar V.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2021)
Heterogeneous catalysis has been utilized in number of efficient reactions with higher selectivity of the product, more stable, reusable and easy for separation as compared to homogeneous catalysts. Generally, heterogeneous catalysts are prepared by using mesoporous materials, microporous materials, metal oxides and metal organic framework. The mesoporous materials have small particle size and high surface area as compared to the microporous materials. The adsorbent mesoporous materials have highly efficient for the therapeutic applications in chemistry hence it has best as compared to other heterogeneous materials. Herein, we have reported synthesis of 1,4-dihydropyridines and polyhydroquinolines at solvent free and environmental benign condition in the presence of Zn/MCM-41 catalyst. The present protocol gives excellent yield (89-96%) of the product within short reaction time by easy work up procedure and no need of further purification of product. The catalyst was characterized by XRD diffractometer, SEM, EDAX, TGA-DTA, BET surface area analysis and FT-IR Spectroscopy. The synthesized organic compounds were characterized by FT-IR, H-1 NMR, C-13 NMR, LC-MS spectrometry.
Keywords: High activity; High selectivity; mesoporous materials; microporous materials; Reusability of catalyst

Efficient and convenient heterogeneous Cu/MCM-41 catalyst for the synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives - Dhengale, Shankar D.; Bhosale, Tanaji R.; Shinde, Sachin B.; Rode, Chandrashekhar V.; Kolekar, Govind B.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2023)
An efficient and convenient method for synthesis of 7,10,11,12-tetrahydrobenzo[c]acridin-8(9H)-one derivatives using Cu/MCM-41 (20 mg) as heterogeneous catalyst. The advantages have an excellent product yield within a short time and easy work-up procedure, and the products have directly recrystallized from hot methanol with cost-effective catalyst. One-pot three-component reaction from aromatic aldehydes, cyclic 1,3-dicarbonyl compounds, and 1-naphthyl amine has been carried under ethanol as a solvent with reflux condition. Moreover, the catalyst can be recovered conveniently and reused efficiently, and recyclable. [GRAPHICS] .
Keywords: Benzo[c]acridine; dimedone; Heterogeneous Cu/MCM-41 catalyst; Multicomponent one-pot reaction